2013
DOI: 10.1155/2013/825376
|View full text |Cite
|
Sign up to set email alerts
|

Exact Analytical Solution of the Peristaltic Nanofluids Flow in an Asymmetric Channel with Flexible Walls and Slip Condition: Application to the Cancer Treatment

Abstract: In the cancer treatment, magnetic nanoparticles are injected into the blood vessel nearest to the cancer's tissues. The dynamic of these nanoparticles occurs under the action of the peristaltic waves generated on the flexible walls of the blood vessel. Studying such nanofluid flow under this action is therefore useful in treating tissues of the cancer. In this paper, the mathematical model describing the slip peristaltic flow of nanofluid was analytically investigated. Exact expressions were deduced for the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…Further investigations of nanofluids in biomedical applications include Anghel and Grumezescu [9] who have demonstrated the excellent bacterial adherence (biofilm) inhibiting characteristics of nanofluid oils in the smart design of novel material surfaces for prosthetic devices. Other analytical articles considering nanofluid dynamics in medicine include Ebaid and Aly [10] for peristaltic flows, Akbar et al [11] for curved tube peristaltic transport of copper nanofluids, Saurin et al [12] for ionic nanofluid bio-lubrication systems (hip joints), Bég et al [13] for swirling mixing systems in nano-biopolymers and very recently Uddin et al [14] for gyrotactic bioconvection in slip Sakiadis flows of nano-polymer sheet manufacturing processes. In the context of cilia hydrodynamics, several studies addressing nanofluid transport have also been communicated.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Further investigations of nanofluids in biomedical applications include Anghel and Grumezescu [9] who have demonstrated the excellent bacterial adherence (biofilm) inhibiting characteristics of nanofluid oils in the smart design of novel material surfaces for prosthetic devices. Other analytical articles considering nanofluid dynamics in medicine include Ebaid and Aly [10] for peristaltic flows, Akbar et al [11] for curved tube peristaltic transport of copper nanofluids, Saurin et al [12] for ionic nanofluid bio-lubrication systems (hip joints), Bég et al [13] for swirling mixing systems in nano-biopolymers and very recently Uddin et al [14] for gyrotactic bioconvection in slip Sakiadis flows of nano-polymer sheet manufacturing processes. In the context of cilia hydrodynamics, several studies addressing nanofluid transport have also been communicated.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Baskar et al discussed the relationship between cancer and radiation therapy in a novel method and found that the radiation can be delivered with the integration of molecular targeted therapy and the therapeutic ratio of the radiation treatment. For more details in this direction see Delaney et al, Ebaid and Aly, Jackson and Bartek, and Bernier et al…”
Section: Introductionmentioning
confidence: 99%
“…The peristaltic transport of nanoparticles has applications in the treatment of malignant tumors, magnetic resonance imaging to diagnose bleeding reduction during diseases, in cancer therapy, and in the transport of drugs. In view of this, important contributions of peristaltic transport of nanofluids have been studied [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%